Cessation of Deliberate Self-Harm Behavior in Patients With Borderline Personality Traits Treated With Outpatient Dialectical Behavior Therapy - Westad, Yngvill Ane Stokke; Hagen, Kristen; Jonsbu, Egil; Solem, Stian (Frontiers in Psychology, 2021)
The first aim of the study was to identify when deliberate self-harm (DSH) behavior ceased in patients with borderline symptoms undergoing dialectical behavioral treatment (DBT). The second aim was to compare patients who ceased their self-harm behavior early or late in the course of treatment, with regard to demographics, comorbidity, and symptom severity. The study used a naturalistic design and included 75 treatment completers at an outpatient DBT clinic. Of these 75 patients, 46 presented with self-harming behavior at pre-treatment. These 46 participants where split into two groups, based on median amount of time before ceasing self-harm behavior, termed early (up to 8 weeks) and late (8 + weeks) responders. Treatment duration varied from 16 to 160 weeks. Patients were assessed pre- and post-treatment using measures of depression, hopelessness, personality traits, quality of life, and global assessment of symptoms and functioning. The majority (93.5 %) ceased their self-harming within the first year, and the average number of weeks was 15.5 (SD = 17.8). Twenty-five percent of patients ceased their DSH behavior during the first week of treatment. For the remaining patients, the cessation of DSH continued gradually across a 1-year period. We found no differences between early and late responders with respect to demographics, comorbidity, symptom severity, or treatment outcome. None of the patients committed suicide. The findings indicate that self-harming behavior decreases gradually across the first year after starting DBT.